RELATIONSHIP BETWEEN CHILDREN PARENTS AND SELF-REGULATION WITH CYBERBULLYING TRENDS IN ADOLESCENTS - Muarifah, Alif; Robiah Adawiyah, Siti; Barida, Muya (International Journal of Psychosocial Rehabilitation, 2020)
This study examines the relation between the attachment of child-parents and self-regulation with the tendency of cyberbullying in adolescents. This research involved 174 students in Yogyakarta City. The respondents filled out the parent-child attachment scale, the self-regulation scale, and the cyberbullying tendency scale. This study uses a quantitative correlational approach with a multiple linear analysis technique. The analysis of the major hypothesis shows that the attachment of parent-child and self-regulation correlate very significantly with a cyberbullying tendency of 0.302 (p < 0.00). The analysis of the minor hypothesis shows that the attachment of parent-child is negatively correlated and very significant with the cyberbullying tendency of -0.230 (p < 0.00). Self-regulation is negatively related and highly significant with the cyberbullying tendency of -0.224 (p < 0.00).